PENGARUH KOMPETENSI, MOTIVASI DAN DUKUNGAN ORGANISASI TERHADAP KINERJA PEGAWAI BAGIAN KEUANGAN (Studi Pada Organisasi Perangkat Daerah Se-Kabupaten Lombok Timur) - Muhammad Iswadi; surati surati; hermanto hermanto (Master of Management, Mataram University, 2017)
This research is aimed at analyzing the effect of competence, motivation and organizational support on the performance of financial officers at the Governmental Organization of East Lombok District. This research is an quantitative associative reseach, using primary and secondary data source. The data were collected through questionnaires, interviews and documentation. The population are all 224 employees of Finance Manager at the collection methodused in this research is census method. The data analysis was using multiple regression.The reseach showed that the competence had positive and significant effect on the performanc , motivation had positive and significant on the performancce, and organizational support had positive and significant on performance. It is suggested that employees improve their competence to be better such as improving the abilityto manage the work to be completed on time and that the organization of the district apparatus in East Lombok continue to provide motivation and passion to the financial officers. In addition, the organizational support provided by the district apparatus organization of East Lombok had been in the category of supporting. Thus each agency that has financial officers needs to maintain such supports as the opportunities for training, the opportunities to be promoted an to keep the work environment of financial officers at the regional apparatus organization in the goverment of East Lombok District. Then it is necessary to improve the performance of employees, to have initiative to finish job without having to wait for command from the boss and to dare to take decisions in accordance with the main tesk and function.Keywords: Competence, Work Motivation, Organizational Support and Performance